Recent Progress in Endothelial Progenitor Cell Culture Systems: Potential for Stroke Therapy - TAKIZAWA, Shunya (Neurol Med Chir (Tokyo), 2016)
Endothelial progenitor cells (EPCs) participate in endothelial repair and angiogenesis due to their abilities to differentiate into endothelial cells and to secrete protective cytokines and growth factors. Consequently, there is considerable interest in cell therapy with EPCs isolated from peripheral blood to treat various ischemic injuries. Quality and quantity-controlled culture systems to obtain mononuclear cells enriched in EPCs with well-defined angiogenic and anti-inflammatory phenotypes have recently been developed, and increasing evidence from animal models and clinical trials supports the idea that transplantation of EPCs contributes to the regenerative process in ischemic organs and is effective for the therapy of ischemic cerebral injury. Here, we briefly describe the general characteristics of EPCs, and we review recent developments in culture systems and applications of EPCs and EPC-enriched cell populations to treat ischemic stroke.